Harassment disparities and risk profile within lesbian, gay, bisexual and transgender Spanish adult population: Comparisons by age, gender identity, sexual orientation, and perpetration context - Devís-Devís, José; Pereira-García, Sofía; Valencia-Peris, Alexandra; Vilanova, Anna; Gil-Quintana, Javier (Frontiers in Public Health, 2022)
Lesbian, Gay, Bisexual and Transgender (LGBT) harassment disparities have become a public health issue due to discrimination and the effects on these people’s health and wellbeing. The purpose was to compare harassment disparities within the Spanish adult LGBT population according to age, gender identity, sexual orientation and the context of perpetration and to describe the harassment risk profile. A sample of 1051 LGBT adults participated in a cross-sectional study. Frequencies, percentages and Chi-square tests of independence for stablishing significant differences (p<0.05) were calculated. The corrected standardized residuals allowed to identify the categories in which significant differences emerged. Binomial logistic regression was used to define the probability of the main LGBT groups of suffering harassment. Results show that 54.4% of the participants had experienced harassment. Young adults presented a higher prevalence than the older group. There were significant harassment differences between transgender (67.2%) and cisgender (52.7%) groups, being transgender women the group with the highest percentage of harassment and cisgender LB women the lowest. The main disparities according to sexual orientation emerged between trans lesbians and the other LGB groups. Most harassment occurred in educational contexts and public spaces. Trans women and trans non-binary reported a higher rate of harassment than cis LGB persons in all contexts. Trans people with different orientations (especially transgender lesbians and gays) differed in harassment from LGB cis in four of the six contexts analyzed. Harassment is likely to diminish between 2-3% each year as LGBTs get older in educational contexts and public spaces but increases 1.07 times in the workplace. Trans women, trans non-binary, lesbians and trans men were more likely to suffer harassment than bisexual cis persons. Trans women present the highest risk of harassment in three contexts (workplace, family and public spaces) and trans non-binary in the other three contexts (education, health and sport). Harassment is a serious problem for LGBT adults in Spain, especially among trans people, which differ in characteristics from those of the sexual minorities mainstream. Programs and policies targeted for improving health should therefore consider the differences that came to light in this study.